2014
DOI: 10.3109/08820139.2014.910022
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometry and Solid Organ Transplantation: A Perfect Match

Abstract: In the field of transplantation, flow cytometry serves a well-established role in pre-transplant crossmatching and monitoring immune reconstitution following hematopoietic stem cell transplantation. The capabilities of flow cytometers have continuously expanded and this combined with more detailed knowledge of the constituents of the immune system, their function and interaction and newly developed reagents to study these parameters have led to additional utility of flow cytometry-based analyses, particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 109 publications
0
19
0
1
Order By: Relevance
“…Phospho-specific flow cytometry of the intracellular signaling molecules p38MAPK, ERK and Akt is a promising technique to monitor the pharmacodynamic effects of immunosuppressive drugs in whole-blood of kidney transplant patients 27 . Previous studies on phospho-specific flow cytometry have demonstrated that TAC can inhibit p38MAPK in a dose-dependent manner in kidney transplant patients 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Phospho-specific flow cytometry of the intracellular signaling molecules p38MAPK, ERK and Akt is a promising technique to monitor the pharmacodynamic effects of immunosuppressive drugs in whole-blood of kidney transplant patients 27 . Previous studies on phospho-specific flow cytometry have demonstrated that TAC can inhibit p38MAPK in a dose-dependent manner in kidney transplant patients 28 .…”
Section: Introductionmentioning
confidence: 99%
“…В ряде зарубежных публикаций представлены доказательства клинической информативности исследования клеточной составляющей иммунного статуса пациентов для определения лечебной тактики, режимов введения иммуносупрессивной и противоинфекционной терапии при пересадках солидных органов [9][10][11].…”
Section: Conclusion the Changes Revealed In The Cellular Component Ounclassified
“…To apply FCXM, donor lymphocytes and recipient serum samples were utilized. Subsequently, antihuman IgG antibodies are added and positivity is determined [10]. In addition, to add CD3 or CD19, T cells and B cells can be separated and analyzed simultaneously (Figure 2).…”
Section: Flow Cytometry Crossmatchmentioning
confidence: 99%